A Research on Online Education Behavior and Strategy in University - Deng, Quan (Frontiers in Psychology, 2022)
After the reform and opening up in China, through a series of rapid developments in world, online education has grown both socially and economically. This area has become representative of the fast-growing economy. However, Guangfu culture as a crucial component of Cantonese traditional culture is gradually becoming less influential today. It is the college's responsibility and duty to protect, carry forward, and inherit this traditional culture. Especially during this cyber era, where networks have become a powerful source for communication and study, there are diversified methods of adaptive learning and various learning behaviors. This article aims to analyze the plausibility of adapting an online platform into the teaching arena and the needs of students under this teaching mode. A simulation of applying advanced technology and artificial intelligence into Guangfu culture innovation was also conducted. The contribution shows the users in this platform have a longer study time, compared with non-platform users, and are more interested in traditional culture knowledge than non-users; 21.5% higher in the performance's test.